Evaluation of the annual electricity production of a hybrid breakwater-integrated wave energy converter. (15th December 2020) - Calheiros-Cabral, Tomás; Clemente, Daniel; Rosa-Santos, Paulo; Taveira-Pinto, Francisco; Ramos, Victor; Morais, Tiago; Cestaro, Henrique
Abstract: Ocean waves constitute an abundant source of clean and predictable energy, with the potential to partly replace carbon intensive energy sources. At present, several technologies to convert wave energy into electricity are being developed, but those suitable for integration into port breakwaters present additional advantages. This paper presents a novel concept that combines two well-known wave energy conversion principles, an oscillating water column and a multi-reservoir overtopping system. This hybrid concept was designed to be integrated in rubble-mound breakwaters, having as case study Leixões' northern breakwater, Portugal. The performance and efficiency of the single components were assessed separately as well as that of the hybrid module as a whole, to demonstrate the advantages of their combination into a single unit. Furthermore, the annual energy production was estimated for a 20 m wide hybrid module considering the local metocean conditions. Results showed that overall efficiency amounted to circa 44.4%, the wave-to-wire efficiency to 27.3% and the annual electricity production was estimated at 35 MWh/m. Considering that 240 m of the reference breakwater are used, the developed hybrid module could provide approximately 50% of the electricity consumption of the Port of Leixões, which demonstrates the potential and interest of the developed technology. Highlights: A novel breakwater-integrated hybrid WEC was developed using composite modelling. The device was tested for the wave and tide conditions of the NW coast of Portugal. The hydraulic/pneumatic and overall efficiencies reached 44% and 27%, respectively. A 240 m long hybrid WEC could provide half of the case study port's energy demand. The hybrid WEC is scalable/modular and adaptable to other rubble-mound breakwaters.